2016
DOI: 10.1161/jaha.115.002815
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Mesenchymal Stromal Cells Transplanted Onto the Heart Surface Achieve Therapeutic Myocardial Repair Despite Immunologic Responses in Rats

Abstract: BackgroundTransplantation of allogeneic mesenchymal stromal cells (MSCs) is a promising treatment for heart failure. We have shown that epicardial placement of cell sheets markedly increases donor cell survival and augments therapeutic effects compared with the current methods. Although immune rejection of intramyocardially injected allogeneic MSCs have been suggested, allogeneic MSCs transplanted on the heart surface (virtual space) may undergo different courses. This study aimed to elucidate immunologic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…One particularly attractive application is in cardiovascular disease, the leading cause of mortality in countries with developed and emerging economies3. Indeed, a progressively increasing number of studies has focused on the ability of MSCs to repair the damaged myocardium in murine models of hypertension and heart failure45. Furthermore, in recent years, we and others have tested the efficacy of MSCs for attenuating cardiac and renal injury in large animal models of cardiovascular disease6.…”
mentioning
confidence: 99%
“…One particularly attractive application is in cardiovascular disease, the leading cause of mortality in countries with developed and emerging economies3. Indeed, a progressively increasing number of studies has focused on the ability of MSCs to repair the damaged myocardium in murine models of hypertension and heart failure45. Furthermore, in recent years, we and others have tested the efficacy of MSCs for attenuating cardiac and renal injury in large animal models of cardiovascular disease6.…”
mentioning
confidence: 99%
“…In a study by Tano et al myocardial function, cell survival and tissue regeneration were compared following cell therapy through intra‐myocardial injection and epicardial cell‐sheet implantation (scaffold free). This demonstrated enhanced cardiac function and tissue structure as well as higher cell survival in the epicardial implantation approach as compared with intra‐myocardial injection of MSCs …”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated enhanced cardiac function and tissue structure as well as higher cell survival in the epicardial implantation approach as compared with intra-myocardial injection of MSCs. 15 To ameliorate stem cell engraftment, several approaches have been investigated including genetic manipulation of cells to increase homing and survival as well as tissue engineering techniques involving preparation of scaffolds. 5,[16][17][18][19] Scaffolds that are derived from decellularized natural tissues appear to be appropriate and efficient as they possess the essential natural tunnels for vessels and nerves as well as the porosity to nest-specific cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…We must be aware that the safety of such cell sheet should be carefully checked before clinical application. Tano and his colleagues reported that allogeneic rat mesenchymal stromal cells improved cardiac function to an equivalent degree compared to syngeneic MSC sheet despite an immunologic response without immunosuppressive drugs [96].…”
Section: Immunological Rejectionmentioning
confidence: 99%